Identification of lambda-cyhalothrin residues on Chinese cabbage using fuzzy uncorrelated discriminant vector analysis and MIR spectroscopy - Wu, Xiaohong; Zhang, Tingfei; Wu, Bin; Zhou, Haoxiang (International Journal of Agricultural and Biological Engineering, 2022)
Excessive pesticide residues on Chinese cabbage will be harmful to people’s health. Therefore, an identification system was designed for qualitative analysis of lambda-cyhalothrin residues on Chinese cabbage leaves. In order to extract discriminant information from mid-infrared (MIR) spectra of Chinese cabbage effectively, fuzzy uncorrelated discriminant vector (FUDV) analysis was proposed by introducing the fuzzy set theory into uncorrelated discriminant vector (UDV) analysis. In this system, the Cary 630 FTIR spectrometer was used to scan four samples of Chinese cabbage with different concentrations of lambda-cyhalothrin. The MIR spectra were preprocessed by standard normal variable (SNV) and Savitzky-Golay smoothing (SG). Next, the high-dimensional MIR spectra were processed for dimension reduction by principal component analysis (PCA). Furthermore, UDV, FUDV, and some other discriminant analysis algorithms were used for feature extraction, respectively. Finally, the K-nearest neighbor (KNN) classifier was employed to classify the data. The experimental results showed that when FUDV was used as the feature extraction algorithm, the identification system reached the maximum classification accuracy of 100%. The results indicated that FUDV combined with MIR spectroscopy was an effective method to identify lambda-cyhalothrin residues on Chinese cabbage. Keywords: Chinese cabbage, mid-infrared spectroscopy, fuzzy uncorrelated discriminant vector, uncorrelated discriminant vector, lambda-cyhalothrin residues DOI: 10.25165/j.ijabe.20221503.6486 Citation: Wu X H, Zhang T F, Wu B, Zhou H X. Identification of lambda-cyhalothrin residues on Chinese cabbage using fuzzy uncorrelated discriminant vector analysis and MIR spectroscopy. Int J Agric & Biol Eng, 2022; 15(3): 217–224.